2017
DOI: 10.1021/acsami.7b13672
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterning of a Stimuli-Responsive Fluorescent Supramolecular Polymer by Thermal Scanning Probe Lithography

Abstract: The miniaturization of nanometer-sized multicolor fluorescent features is of continuous significance for counterfeit security features, data storage, and sensors. Recent advances in engineering of stimuli-responsive supramolecular polymeric materials that respond upon exposure to heat or mechanical force by changing their fluorescence characteristics open new opportunities as functional lithographic resists. Here, we demonstrate the patterning of a thermochromic supramolecular material by thermal scanning prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…b Conversion of a functional material from a precursor 42,45,[86][87][88][89][90][91][92]94,95 . c Amorphization by short heating and fast subsequent quenching to obtain a less ordered phase 96,97 . d Local crystallization of an amorphous material 21,[98][99][100][101][102] .…”
Section: Chemical Conversion Deprotection Of Functional Groupsmentioning
confidence: 99%
“…b Conversion of a functional material from a precursor 42,45,[86][87][88][89][90][91][92]94,95 . c Amorphization by short heating and fast subsequent quenching to obtain a less ordered phase 96,97 . d Local crystallization of an amorphous material 21,[98][99][100][101][102] .…”
Section: Chemical Conversion Deprotection Of Functional Groupsmentioning
confidence: 99%
“…f) Thermal SPL generated fluorescence pattern and corresponding AFM characterization. Adapted under the terms of the ACS AuthorChoice license . Copyright 2017, American Chemical Society.…”
Section: The Role Of Fabrication In Nanotechnologymentioning
confidence: 99%
“…Besides this, SPL can also induce intermolecular changes for patterning of materials other than semiconductors. Zimmermann et al reported the use of SPL to pattern fluorescent polymers by selectively quenching the fluorescent polymer with heat (Figure f) . These fluorescence patterns were used to write QR codes as shown in Figure f, and this concept can be easily extended to the nanoscale for generation of latent (hidden) optical features.…”
Section: The Role Of Fabrication In Nanotechnologymentioning
confidence: 99%
“…The process of patterns' formation mainly relies on the strong contact force between the tip and the sample . ii) Thermal SPL (t‐SPL) : this technique uses a heating probe to alter the properties of the sample locally . iii) Thermochemical SPL (tc‐SPL) : this technique modifies the chemical properties of a material locally by heating; iv) Dip pen SPL (dp‐SPL) : this technique allows depositing of various types of molecules or inks on the surface of the samples .…”
Section: Spm‐based Lithographymentioning
confidence: 99%